2007
DOI: 10.1377/hlthaff.26.5.w630
|View full text |Cite
|
Sign up to set email alerts
|

Medicare Prescription Drug Benefit Progress Report: Findings From A 2006 National Survey Of Seniors

Abstract: W i t h t h e m e di c a r e drug benefit approaching its third year of operation, there is considerable interest in understanding its effects on beneficiaries' coverage, out-of-pocket spending, and access to needed medications. The Part D benefit was enacted to respond to the welldocumented problems facing beneficiaries who lacked drug coverage, particularly those with modest means or high out-of-pocket spending. 1 Since the enactment of the Medicare drug benefit, researchers and policymakers have predicted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
107
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(120 citation statements)
references
References 7 publications
12
107
1
Order By: Relevance
“…Our findings, coupled with those of others (Campbell and Morgan 2007;Neuman et al 2007;Domino et al 2008), raise concerns about beneficiaries' ability to use available information to make the best choice of a Medicare prescription drug plan. Given the importance of drug coverage and the potential saving involved, policy makers should be attuned to these issues and consider ways to make the decision making process easier and more effective.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Our findings, coupled with those of others (Campbell and Morgan 2007;Neuman et al 2007;Domino et al 2008), raise concerns about beneficiaries' ability to use available information to make the best choice of a Medicare prescription drug plan. Given the importance of drug coverage and the potential saving involved, policy makers should be attuned to these issues and consider ways to make the decision making process easier and more effective.…”
Section: Discussionsupporting
confidence: 50%
“…The primary objective evidence so far concerns stickiness--that is, unwillingness to change plans from year to year, even when it is economically wise to do so. Two national surveys found that fewer than one tenth of enrollees switched drug plans during the open enrollment period between the first and second years of the Medicare drug program, and nearly half of those were lowincome beneficiaries who were required to switch because their plan no longer covered them (Campbell and Morgan 2007;Neuman et al 2007). This is of potential concern because plans that may have low costs 1 year often raise their premiums or change their formulary, leading to dramatic increases in premiums the following year (Kritz 2007).…”
Section: Background: Choosing a Medicare Prescription Drug Planmentioning
confidence: 99%
“…15,16 In 2008, an estimated 4.6 million (10%) Medicare beneficiaries had no prescription drug coverage, with nearly 3.3 million of those representing the most vulnerable Medicare beneficiaries who may qualify for the low-income subsidy. 17,18 Additionally, even for the 25 million Medicare beneficiaries enrolled in a Part D plan, the benefit is confusing and complex, and patients' cost-sharing is increasing annually, leading to changes in medicationtaking behaviors. 18,19 The challenges facing those enrolled in Part D, particularly vulnerable patients, require an interprofessional solution.…”
Section: Designmentioning
confidence: 99%
“…17,18 Additionally, even for the 25 million Medicare beneficiaries enrolled in a Part D plan, the benefit is confusing and complex, and patients' cost-sharing is increasing annually, leading to changes in medicationtaking behaviors. 18,19 The challenges facing those enrolled in Part D, particularly vulnerable patients, require an interprofessional solution.…”
Section: Designmentioning
confidence: 99%
“…Most MA-PD plan enrollees were enrolled in an MA plan prior to 2006; 103 these beneficiaries generally experienced a smoother transition to drug coverage with the advent of Part D thanks to the subtle integration of the new benefit into the already existing managed care structure. 59 Further, these plans have been offering more generous drug coverage than Part D stand-alone prescription drug plans (PDP), 103 and their design is associated with much less disparities in access to drugs and benefit information, 59 as well as better coordination of care. 104 Hispanic seniors were more likely to be automatically eligible for the low-income subsidy than blacks and whites (46%, vs. 30 and 8% among blacks and whites, respectively, in our sample).…”
mentioning
confidence: 99%